Does Neuromarketing Matter to Purchase Intention on Coffeeshop Industry? (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2024)
This study aims to explore the impact of neuromarketing elements such as ambience and sensory marketing, and brand perception on consumer purchase intentions within the Indonesian coffee shop industry. By examining these factors, the research seeks to uncover subconscious drivers that shape consumer behavior and provide actionable insights for coffee shop owners. Utilizing a quantitative approach, data were collected from 194 respondents via purposive sampling, analyzed using regression techniques. Results indicate that ambience, sensory marketing, and brand perception significantly influence purchase intentions, explaining 48% of the variance (R² = 0.480), with brand perception being the most dominant factor (β = 0.525). The findings underscore the importance of creating a positive consumer experience through optimized sensory engagement, inviting atmospheres, and strong brand identity. Managerial implications suggest coffee shop owners should invest in sensory marketing strategies and branding efforts to enhance customer satisfaction, loyalty, and long-term competitiveness in an increasingly saturated market.